La lectura crítica y su incidencia en el aprendizaje significativo de los estudiantes de la unidad educativa “Manuel Villamarín Ortiz” parroquia Clemente Baquerizo, cantón Babahoyo, provincia los Ríos - Gaibor Espinoza, Luz Targelia (2017)
In this final document the interested parties will find a classified information about the strategies of reading that contribute to the thought since this investigation was realized in the Educational Unit "Manuel Villamarín Ortiz" of the parish Clemente Baquerizo, canton Babahoyo, province Los Ríos, the same one that served to study the problematic and to verify if the critical reading influences in the significant learning of the students of this institution object of study. In the following chapters we find the explanation of each of the variables and other topics on critical reading and meaningful learning that were studied, and then determine the objectives to be fulfilled of that research, supported by studies by other authors, the Which allowed finding the existing problem, which was simultaneously studied to find a solution through the proposal established in this final report, with which teachers and students of the Educational Unit will benefit.